1973
DOI: 10.1139/y73-061
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Resistance and Na+–K+ Gradients in the Perfused Rat-Tail Artery

Abstract: The changes in the resistance of the perfused ventral rat-tail artery resulting from exposure of the tissue to ouabain-containing and/or K+-free physiological salt solution were studied. In each case, there was an increase in the vascular resistance which was not sustained. The response of the arterial wall to the above stimuli was abolished in the absence of external Ca2+. In contrast to the delayed response of the wall to either ouabain-containing or K+-free solution, an almost instantaneous rise in the resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Haddy and Overbeck (1976) suggested alternatively that calcium influx following sodium pump inhibition takes place through voltage dependent channels (electromechanical coupling). Whichever of the two alternative mechanisms are operative for sodium transport inhibitors, both ouabain-and KoPSSinduced contractions were totally dependent on calcium influx from the outside in this and other studies (Briggs & Shibata 1966;Friedman et al 1973;Ma& Bose 1977). Also KoPSS contractions were dose-dependently inhibited by verapamil and nifedipine suggesting the paramount importance of calcium influx from outside for the production of contraction in anococcygeus by sodium transport inhibitors.…”
Section: Discussionsupporting
confidence: 72%
“…Haddy and Overbeck (1976) suggested alternatively that calcium influx following sodium pump inhibition takes place through voltage dependent channels (electromechanical coupling). Whichever of the two alternative mechanisms are operative for sodium transport inhibitors, both ouabain-and KoPSSinduced contractions were totally dependent on calcium influx from the outside in this and other studies (Briggs & Shibata 1966;Friedman et al 1973;Ma& Bose 1977). Also KoPSS contractions were dose-dependently inhibited by verapamil and nifedipine suggesting the paramount importance of calcium influx from outside for the production of contraction in anococcygeus by sodium transport inhibitors.…”
Section: Discussionsupporting
confidence: 72%
“…However, the vasodilator action of K + has been shown to be transient (131, 373), and higher concentrations of K + (typically > 20 mmol/L) are known to produce vasoconstriction (875). These discrepant findings appear to be related to the effect of K + in setting the basal activity of the Na/K-ATPase (355, 721). Work by the Sparks laboratory demonstrated that K + release quickly declines following increases in heart rate in normally oxygenated hearts (699).…”
Section: Metabolic Control Of Coronary Blood Flowmentioning
confidence: 95%
“…The Na + record thus is not always as simple to interpret or as accurate as that for K+. 11 In a recent report describing the use of inulin to identify extracellular cations, 14 we noted that during the enrichment of cells with Na that results from exposure to ouabain, the deviation of the Na + -K + exchange from an approximate equimolar ratio is very small. Later, we drew a similar conclusion from experiments in which tissues were incubated in a K + -free medium and cold LiPSS was used to identify cell Na.…”
Section: Comparison Of Na+-k+ Exchange In Incubated and Perfused Normmentioning
confidence: 98%